Adult primary angiitis of the central nervous system: isolated small-vessel vasculitis represents distinct disease pattern. (3rd December 2016) - de Boysson, Hubert; Boulouis, Grégoire; Aouba, Achille; Bienvenu, Boris; Guillevin, Loïc; Zuber, Mathieu; Touzé, Emmanuel; Naggara, Olivier; Pagnoux, Christian
Abstract : Objectives. We aimed to identify whether presentations and outcomes in adult patients with isolated small-vessel primary angiitis of the CNS (PACNS) would differ from other patients with large/medium-vessel involvement. Methods. In the French PACNS cohort, we compared the characteristics, treatments and outcomes of patients with isolated small-vessel disease (normal CT, MR and/or conventional angiograms, brain biopsy positive for vasculitis) with other patients who had large/medium-vessel involvement (vessel abnormalities on CT, MR or conventional angiograms). A good functional outcome was defined as a modified Rankin scale ⩽2 at last follow-up, regardless of the occurrence of relapse. Results. Among the 102 patients in the cohort, 26 (25%) had isolated small-vessel PACNS, whereas the 76 others demonstrated large/medium-vessel involvement. Patients with isolated small-vessel PACNS had more seizures (P < 0.0001), cognitive (P = 0.02) or consciousness impairment (P = 0.03) and more dyskinesias (P = 0.002) but less focal deficits (P = 0.0002) than other PACNS patients. They also had more abnormal cerebrospinal fluid analysis (P = 0.008) and gadolinium enhancements on MRI (P = 0.001) but less frequent acute ischaemic lesions (P < 0.0001) than patients with large/medium-vessel involvement. Treatments and modified Rankin scale at last follow-up did not differ between groups. Thirty-two (31%) patients relapsed; 14 (54%) with isolated small-vessel PACNS vs 18 (24%) with large/medium-vessel involvement (P = 0.004). Eight patients died, with no difference between the groups (P = 0.97). Conclusion. In our cohort, adult patients with isolated small-vessel PACNS presented some distinct disease features and relapsed more often than other PACNS patients who had large/medium-vessel involvement. Functional outcomes and mortality did not differ.